2018
DOI: 10.4103/abr.abr_17_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTX-M and TEM β-lactamases in Klebsiella pneumoniae Isolates from Patients with Urinary Tract Infection, Al-Zahra Hospital, Isfahan, Iran

Abstract: Background:Extended-spectrum β-lactamase (ESBL)-producing is a significant resistant mechanism to β-lactams in Enterobacteriaceae, especially in Klebsiella pneumoniae. The main objectives of this study were to genetically characterize urinary clinical isolates of K. pneumoniae through the investigating of blaTEM, blaCTX-M and using molecular typing by Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) method. We also determined the frequency of antibiotic resistance of K. pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
3
5
2
Order By: Relevance
“…The current study showed the occurrence of 100% for MDR K. pneumoniae strains, but in other studies conducted in Iran, the frequency of these strains was reported to be 74% and 46.6%, which is less than our results [28, 29]. The possible explanation for this higher rate of MDR characteristic, mainly in developing countries, could be irregular antibiotic prescription, sampling biases, genetic variations, geographic differences, social behaviors, and dissimilar patients' characteristics [28].…”
Section: Discussioncontrasting
confidence: 96%
“…The current study showed the occurrence of 100% for MDR K. pneumoniae strains, but in other studies conducted in Iran, the frequency of these strains was reported to be 74% and 46.6%, which is less than our results [28, 29]. The possible explanation for this higher rate of MDR characteristic, mainly in developing countries, could be irregular antibiotic prescription, sampling biases, genetic variations, geographic differences, social behaviors, and dissimilar patients' characteristics [28].…”
Section: Discussioncontrasting
confidence: 96%
“…Based on the previous studies, the frequency of MDR in the ESBL-producing K. pneumonia isolates ranges from 63.33 to 92%. That is consistent with the findings of the current study (5,(20)(21)(22). Accordingly, more than 86% of ESBLproducing strains were resistant against cephalosporins.…”
Section: Discussionsupporting
confidence: 93%
“…Along with other gram-negative bacteria such as Pseudomonas aeruginosa and Acinetobacter baumannii, K. pneumonia pathogens are commonly isolated from patients with burn infections (4). Most of such infections are caused by multidrug-resistant (MDR) strains that interrupt the treatment processes (5). Besides, extended-spectrum beta-lactamase (ESBL)producing K. pneumonia isolates are highly resistant to antibiotics, which further complicate infections and the treatment processes of burn patients.…”
Section: Introductionmentioning
confidence: 99%
“…pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018). PFGE and ERIC-PCR analysis in these studies showed the presence of different clones in each clinical center (Akya et al, 2018; Hashemizadeh et al, 2018; Kiaei et al, 2018; Maleki et al, 2018). This is with the exception of one study where high clonal relatedness among ESBL K. pneumoniae strains was reported (Ghaffarian et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 71%
“…In Iran, studies have shown that in Klebsiella spp., resistance to extended spectrum beta lactams is mainly mediated via the production of CTX-M variants (CTX-M-15, CTX-M-3, CTX-M-8, CTX-M-1, and CTX-M-2) (Feizabadi et al, 2010; Peerayeh et al, 2014; Bialvaei et al, 2016; Akya et al, 2018; Dehshiri et al, 2018) and to a lesser degree via SHV (SHV-12, SHV-11, SHV-5) (Feizabadi et al, 2010; Shakib et al, 2018), TEM genes (Gholipour et al, 2014; Maleki et al, 2018) and others (VEB, PER, and GES) (Sedighi et al, 2017). pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%